Institutional Performance and Tourism Arrival Nexus in BRICS Countries: Evidence from Nonlinear ARDL Cointegration Approach - Awan, Ayesha; Rahman, Saif Ur; Ali, Mubashar; Zafar, Mahwish (iRASD Journal of Economics, 2023)
Tourism is significantly influenced by institutional quality. The strength of institutions is also important for the growth of tourism because poor institutions may inhibit tourists from entering a region. Over the years, there have been rare studies on the association between institutional quality and tourism in BRICS Nations by using NARDL. Using the NARDL model & institutional theories, this study looks at the asymmetric effects of institutional quality on tourist arrival in the BRICS countries from 1996 to 2021. The findings suggest that a gain in institutional quality will boost Tourist arrival for the BRICS countries to examine the interrelationships among variables both long and short run and NARDL shows a positive relation between the expansion of tourism in the BRICS countries. This study examines the asymmetric effects of institutional quality and energy consumption on visitor arrival. The long-run asymmetries between institutional quality, energy use, and tourism in the BRICS countries. Furthermore, the study finds that neglecting the series’ inherent nonlinearities may lead to misleading inferences. The policy argued that in order to increase investment in institutional quality and energy consumption, appropriate measures must be taken, including deregulation of economic activity, the development of The implementation of adequate regulatory frameworks and tax constructions, the development of port infrastructure, a road network, a rail system, and telecommunications facilities, the achievement of trade-related clarity trade-related adaptability and the expansion of the nation's infrastructure in to accommodate more tourists. As a result, recommendations for measures to improve tourist arrival, promote high-quality institutions, and stop environmental damage were suggested. As a result, the present study offers the BRICS countries a foundation for their policies.